Pengaruh Penggunaan Multi Media Terhadap Pembelajaran Berbicara Bahasa Inggris Pada Siswa SMA - Yunisa Varera (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The development of information technology in the form of social media has experienced tremendous progress throughout the world. This development has an impact on changes in social behavior. Social behavior is defined as individual behavior in relation to society, or among members of society in the context of how they communicate between its members. The use of YouTube, Facebook, blogging, WhatsApp and Twitter for learning purposes by creating groups based on certain interests to hold discussions is very widespread in society. As a result of the very rapid development of social media, social behavior patterns have changed, which has gradually led to the integration of social media applications in various types of learning and learning activities. In fact, overall it can be said that this change is a change in the education system which covers all components